Abraham Lincoln's dueling words - Bowman, Donna Janell (Peachtree Publishers, 2018)
Abraham Lincoln was known for his sense of humor. But in 1842, early in his adult life, it nearly got him into trouble. He had to use his imagination to save his career--and maybe even his life.